2012
DOI: 10.3758/s13423-012-0232-z
|View full text |Cite
|
Sign up to set email alerts
|

Geometric orientation by humans: angles weigh in

Abstract: Human participants were trained to navigate to two geometrically equivalent corners of a parallelogramshaped virtual environment. The unique shape of the environment combined three distinct types of geometric information that could be used in combination or in isolation to orient and locate the goals: the angular amplitudes of the corners, the relative wall length relationships, and the principal axis of symmetry. In testing, participants were placed in manipulated versions of the training environment that tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 27 publications
3
26
3
Order By: Relevance
“…A growing number of studies have shown that reorientation by human and non-human animals is highly sensitive to alterations in local geometry and our results add to this body of research [7], [10], [11], [28], [29]. During testing in the L-shaped environment, participants directed the majority of their searches to the corners that matched the medial axes of the training environment.…”
Section: Discussionmentioning
confidence: 51%
“…A growing number of studies have shown that reorientation by human and non-human animals is highly sensitive to alterations in local geometry and our results add to this body of research [7], [10], [11], [28], [29]. During testing in the L-shaped environment, participants directed the majority of their searches to the corners that matched the medial axes of the training environment.…”
Section: Discussionmentioning
confidence: 51%
“…These findings are puzzling, however, not only because they seem to contradict the Jacobs and Schenk hypothesis, but also because Sutton, Twyman, Joanisse and Newcombe (2012) found that, at least in virtual reality, adults could infer the global geometric shape from and array of four columns. Additionally, Lubyk, Dupuis, Gutiérrez, and Spetch (2012) found that adults were able to reorient with local acute and obtuse angles in a virtual reality search task, and importantly, no sex differences were found.…”
Section: Local Versus Global Geometrymentioning
confidence: 95%
“…As previously discussed, there is ample evidence that geometric distance cues are a prominent cue for reorientation in many species, and these cues are assumed by Spelke and colleagues (2010) to be part of the core geometry system, whereas the role of angles in reorientation is less clear. Although adult humans can readily reorient by angular information (Lubyk, Dupuis, Gutiérrez, & Spetch, 2012;Lubyk, Spetch, Zhou, Pisklak, & Mou, 2013), Spelke et al (2010) suggested that angular information is not part of the core system based on developmental data, and Sturz, Forloines, and Bodily (2012) have provided evidence suggesting that corner angles may function as featural cues. Thus, the priority given to height cues may differ depending on the type of horizontal cue that is concurrently available during the learning phase.…”
mentioning
confidence: 99%